An unorthodox approach to the spoken language and the people who speak it (New York, 1968)
This book for students of the Japanese language and for others having a general interest in Japan and its people . The contens this book advice about how to study the Japanese language, how to derive enjoyment from these studies,...
Keywords: Japanese language,National characteristics, japanese,Japan; Miscellanea,Miscellanea,Social life and customs,Miscellanea